2016
DOI: 10.1016/j.apergo.2016.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Occupational sitting behaviour and its relationship with back pain – A pilot study

Abstract: Nowadays, working in an office environment is ubiquitous. At the same time, progressively more people suffer from occupational musculoskeletal disorders. Therefore, the aim of this pilot study was to analyse the influence of back pain on sitting behaviour in the office environment. A textile pressure mat (64-sensor-matrix) placed on the seat pan was used to identify the adopted sitting positions of 20 office workers by means of random forest classification. Additionally, two standardised questionnaires (Korff,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 40 publications
0
40
0
4
Order By: Relevance
“…Prior to the experiment, the representative sitting posture was defined with reference to previous studies on sitting postures. From these previous studies, the present study derived representative sitting postures, such as the sitting posture in the forward position, middle position, or backward position, forward sitting posture, reclined sitting posture, slumped sitting posture, laterally tilted left or right sitting posture, and crossed legs right over left or left over right sitting posture [ 6 , 9 , 16 , 17 ]. This study divided the sitting postures into six types as shown in Figure 1 , assuming representative activities in the workplace while sitting on the office chair, with reference to the posture classifications of the previous studies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior to the experiment, the representative sitting posture was defined with reference to previous studies on sitting postures. From these previous studies, the present study derived representative sitting postures, such as the sitting posture in the forward position, middle position, or backward position, forward sitting posture, reclined sitting posture, slumped sitting posture, laterally tilted left or right sitting posture, and crossed legs right over left or left over right sitting posture [ 6 , 9 , 16 , 17 ]. This study divided the sitting postures into six types as shown in Figure 1 , assuming representative activities in the workplace while sitting on the office chair, with reference to the posture classifications of the previous studies.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies on SPMSs can be classified according to two purposes. The first purpose is to determine whether or not a person is seated on the office chair, which is used mainly to monitor seat occupancy [ 6 , 7 , 8 , 9 ]. The second purpose is to detect various sitting postures in order to identify bad sitting postures; this is commonly implemented by inserting pressure sensors into the backrest plate and seat plate [ 3 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sitting and relief positions during the three measurement weeks were identified using supervised learning with a random forest classifier [26,27]. An individual classifier was generated for every subject using the recordings of the different relief techniques (three measurements each) as well as the upright sitting position acquired during the setup process (similarly to [28]). For every subject-specific classifier an ensemble of 200 bagged decision trees was created while using 60% of the input data for growing each tree (MATLAB's parameter: InBagFraction = 0.6).…”
Section: Data Pre-processingmentioning
confidence: 99%
“…Some of the proposed solutions relied on the use of wearable sensors [22,23,24,25], while others exploited non-invasive approaches in which the sensors were applied on the environment (e.g., chairs [26,27,28,29,30,31,32,33]). In this way, participants were not aware of being monitored, thus allowing the reproduction of real-life conditions.…”
Section: Introductionmentioning
confidence: 99%